Persistent Organic Pollutants in Streamwater: Influence of Hydrological Conditions and Landscape Type - Josefsson, Sarah; Futter, Martyn; Bergknut, Magnus; Jansson, Stina; Laudon, Hjalmar; Lundin, Lisa; Wiberg, Karin (2016)
Concentrations of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), and hexachlorobenzene (HCB) in streamwater were measured in a remote catchment in northern Sweden and downstream to the Baltic Sea. Sampling took place at seven sites during two years and under different hydrological conditions: during the snow-free, snow-covered, and spring-flood seasons. Concentrations varied substantially between seasons and were up to 20 times higher during the spring flood compared to the preceding snow-covered period. The increase in concentrations with runoff was due to higher levels of particle-associated contaminants, while the dissolved concentrations remained stable. Particulate-contaminant concentrations were positively correlated primarily to suspended particulate matter (SPM) at sites in areas with a high land-cover fraction of sorted sediment. When upstream sampling locations were compared, a mire-dominated stream had higher concentrations and a lower retention of atmospherically deposited contaminants than a forest stream of the same catchment size. Contaminant concentrations (normalized to volume) did not increase consistently downstream despite the presence of several point sources. However, when normalized to the amount of SPM, concentrations were on average >20 times higher at the outlet in the Baltic Sea compared to the outlet from the remote catchment without point sources.